Unreported exclusion and sampling bias in interpretation of randomized controlled trials in patients with STEMI. (15th August 2019) - Laursen, Peter Nørkjær; Holmvang, Lene; Lønborg, Jacob; Køber, Lars; Høfsten, Dan E.; Helqvist, Steffen; Clemmensen, Peter; Kelbæk, Henning; Jørgensen, Erik; Lassen, Jens Flensted; Pedersen, Frants; Høi-Hansen, Thomas; et al.
Abstract: Aims: To assess the impact of sampling bias due to reported as well as unreported exclusion of the target population in a multi-center randomized controlled trial (RCT) of ST-elevation myocardial infarction (STEMI). Methods and Results: We compared clinical characteristics and mortality between participants in the DANAMI-3 trial to contemporary non-participants with STEMI using unselected registries. A total of 179 DANAMI-3 participants (8%) and 617 contemporary non-participants (22%) had died (Log-Rank: P < 0.001) after a median follow-up of 1333 days (range: 1–2021 days). In an unadjusted Cox regression model all groups of non-participants had a higher hazard ratio to predict mortality compared to participants: eligible excluded ( n = 144) (hazard ratio: 3.41 (95% CI: (2.69–4.32)), ineligible excluded ( n = 472) (hazard ratio: 3.42 (95% CI: (2.44–4.80), eligible non-screened ( n = 154) (hazard ratio: 3.37 (95% CI: (2.36–4.82)), ineligible non-screened ( n = 154) (hazard ratio: 6.48 (95% CI: (4.77–8.80). Conclusion: Sampling bias had occurred due to both reported and unreported exclusion of eligible patients and the difference in mortality between participants and non-participants could not be explained only by the trial exclusion criteria. Thus, screening logs may not be suited to address the risks of sampling bias. Highlights: Participants in the DANAMI-3 trial were not representative to the background population with STEMI. Participants in the DANAMI-3 trial were not representative to the per protocol target population. Sampling bias and unreported screening had occurred. Screening logs may not be suitable for addressing issues of external validity.